"Average-Sized" Models Do Sell, But What About in East Asia? A Cross-Cultural Investigation of U.S. and Singaporean Women. Issue 5 (20th October 2019) - Lou, Chen; Tse, Caleb H.; Lwin, May O.
Abstract : In light of a growing consumer and media outcry against using unrealistically thin models in advertisements, global brands are featuring more inclusive model images in their campaigns, including using average-sized models. However, do consumers from different cultures have varying preferences for model size? To investigate the impact of using an average-sized model (versus a thin model) in apparel ads, we first conducted experiments in both an individualistic culture (i.e., United States) and a collectivistic culture in Asia (i.e., Singapore). Our findings demonstrate that U.S. women expressed increased purchase intentions upon seeing an average-sized model (versus a thin model). Their perceived user-imagery congruity (UIC) also mediates the link between model size and purchase intentions. However, Singaporean women did not differ in their responses upon seeing the ad with an average-sized model (versus a thin model). A further investigation among Singaporean women reveals that their societal view of thinness moderates the impact of model size on purchase intentions, with UIC as the underlying mechanism. Our findings offer theoretical and practical implications for cross-cultural advertising and advance the literature on Asian advertising.